Photo-polymerization, swelling and mechanical properties of cellulose fibre reinforced poly(ethylene glycol) hydrogels. (23rd November 2015) - Khoushabi, A.; Schmocker, A.; Pioletti, D.P.; Moser, C.; Schizas, C.; Månson, J.A.; Bourban, P.E.
Abstract: The application of hydrogels as load-bearing biomedical components is often limited by their mechanical properties. Often an attempt to improve a hydrogel's stiffness is accompanied by a loss of toughness and swelling properties. In this work, we show that the addition of nanofibrillated cellulose (NFC) provides a mean to tailor both the swelling and the mechanical properties of the hydrogel. Various volume fractions of NFC were added to poly(ethylene glycol) dimethacrylate (PEGDM) precursors with two different molecular weights (6 and 20 kDa). The viscosity measurements of the precursor solutions indicated that the dispersed NFCs form a network-like structure in the hydrogel precursor. Such a structure, as observed in the photo-rheology experiments, serves as a light-scattering source when the solution is illuminated by UV light, which provides a uniform polymerization of the hydrogel in three-dimension and reduces the curing time. Mechanical properties of the neat and composite hydrogels were characterized using monotonic and cyclic compression tests. NFC reinforcement increases the hydrogel's stiffness by a factor 2 and 3.5 for the PEGDM matrixes with molecular weights of 6 and 20 kDa respectively without compromising their toughness. Moreover, the desired stiffness and swelling properties can be simultaneously achieved by adapting the reinforcement concentration and the hydrogel cross-link density. The obtained composite hydrogels offer enhanced and tuneable properties and are proposed for injectable and photo-curable load-bearing implants.